Effect of in-season neuromuscular and proprioceptive training on postural stability in male youth basketball players - Ondra Lukáš; Petr Nátěsta; Lucia Bizovská; Eliška Kuboňová; Zdeněk Svoboda (Palacký University Olomouc, 2017)
Background: Poor balance ability is a predictor of injuries of the lower extremity. Multi-intervention proprioception preventive programs, comprising balance training, strength, plyometric, agility, running, and stretching exercises, are effective in improving balance ability and reducing the risk of lower extremity injuries in athletes.Objective: The aim of the study was to examine the effect of a 20-week in-season multi-intervention proprioceptive neuromuscular training program on postural stability in male youth basketball players.Methods: Twenty-one elite male youth basketball players were divided into an intervention group (n = 10, age 17.3 ± 1.3 years) and a control group (n = 11, age 16.5 ± 1.8 years). During the in-season period (20 weeks), the intervention group followed a proprioceptive and neuromuscular training program, three times per week and 20 minutes per session. Balance was tested in a quiet unipedal stance (on both the dominant and non-dominant leg) on a foam mat with eyes open, before and after a 20-week period in both groups. The mean velocities in the medial-lateral and anterior-posterior directions and the mean total velocity of the centre of pressure (COP) displacement were obtained with a force platform.Results: The combined effect (pre-post test × group) showed that intervention resulted in significant improvement in the mean COP velocity for both the dominant and non-dominant limb in the anterior-posterior direction (p = .013 and p < .001, respectively) and in the medial-lateral direction (p = .007 and p < .001, respectively) as well as in the total COP velocity (p = .009 and p < .001, respectively). Conclusions: The specific proprioceptive and neuromuscular training had a positive effect on postural stability for both the dominant and non-dominant limb in basketball players.